Bread, Circuses, and the Politics of State-Sponsored Experiences: The Duality of Role - Nwoke, Uzoma Ugochukwu Nwoke (African Journal of Stability and Development (AJSD), 2025)
This paper examines state-sponsored experiences through the case study of the Roman Colosseum, interrogating its dual role as both a political instrument and a site of civic engagement. Built to awe, to distract, and to reaffirm imperial control, it was a spectacle that kept the masses fed, thrilled, and, most importantly, obedient. But was it truly one-sided? This paper explores the paradox of state-sponsored experiences, questioning whether the Colosseum was merely a tool of control or if audiences, in their cheers and jeers, found subtle ways to assert agency. Drawing parallels with modern mega-experiences like the Olympics, Super Bowls, national celebrations, the study examines how governments continue to wield experiences as instruments of influence. Yet, no experience remains fully in the hands of its creators. Whether in ancient Rome or today, audiences reshape meaning, proving that even the most calculated performances of power can produce something far less predictable like citizen’s authentic engagement or social cohesion.